Çoklu uydu verileri ve farklı makine öğrenme modelleri kullanılarak orman toprak üstü biyokütle kestirimi - Özdemir, Eren Gürsoy; Abdikan, Saygın; Özdemir, Eren Gürsoy (IEEE, 2024)
Forests are critical in reducing carbon emissions and increasing carbon sink areas. Understanding, estimating, and mapping forest biomass is vital for the role of forests in the global carbon budget and climate. The progress in satellite technologies and remote sensing systems has emerged as an alternative method for conducting studies on the estimation of above-ground biomass (AGB), diverging from conventional terrestrial approaches. In this study, the effects of band and vegetation index values on Above Ground Biomass (AGB) estimation were investigated in Oriental beech (Fagus orientalis Lipsky.) and Uludağ fir (Abies nordmanniana subsp. Bornmülleriana mattf.) species within the buffer borders of Küre Mountains National Park in the Western Black Sea region using data from the Sentinel-1 radar and Sentinel-2 optical satellite along with Gradient Boosting and Random Forest machine learning methods. The relationships between AGB values obtained from ground sample plot data and the satellite data were examined. The best results for AGB estimation were achieved using the model that incorporated the Sentinel-1 VH backscatter value, Sentinel-2 Band 4 and 11, Enhanced Vegetation Index (EVI), Difference Vegetation Index (DVI), texture measures derived from Sentinel-2 and the Gradient Boosting method (R2=0.71, RMSE= 20.98 t/ha, MAE=17.47 t/ha).

Ormanlar, karbon salınımlarının azaltılması, karbon yutak alanlarının artırılması kapsamında kritik öneme sahiptir. Ormanların küresel karbon bütçesi ve iklimdeki rolü için orman biyokütlesinin yüksek doğruluklu tahmin edilmesi ve haritalandırılmasını anlamak önem taşır. Uydu teknolojilerinin ve uzaktan algılama sistemlerinin gelişmesiyle geleneksel yersel yöntemlerden farklı olarak Toprak Üstü Biyokütle (TÜB) tahmini çalışmaları için alternatif bir yöntem haline gelmiştir. Bu çalışmada, Batı Karadeniz bölgesinde Küre Dağları Milli Parkı tampon sınırları içerisinde, doğu kayını (Fagus orientalis Lipsky.) ve Uludağ göknarı (Abies nordmanniana subsp. Bornmülleriana mattf.) türleri özelinde, Sentinel-1 radar, Sentinel-2 optik uydu verileri ile Gradyan Artırma ve Rastgele Orman makine öğrenme yöntemlerinden yararlanılarak bant, bitki örtüsü indeksi ve doku bilgileri değerlerinin TÜB tahminine etkileri ve yersel örnekleme alan verilerinden elde edilen TÜB değerleri ile ilişkileri araştırılmaktadır. Sentinel-1 VH geri saçılım değeri, Sentinel-2 Bant 4 ve 11, Gelişmiş Bitki İndeksi (EVI), Fark Bitki indeksi (DVI) ve doku özelliklerinin birleşiminin, Gradyan Artırma yöntemi kullanıldığı modelin TÜB kestiriminde en başarılı sonuç elde edilmiştir (R2=0.71, RMSE= 20.98 t/ha, MAE=17.47 t/ha)
The estimation of forest aboveground biomass using multiple satellite data and different machine learning models
Keywords: Satellites; Forests; Laser radar; Estimation; Vegetation mapping; Sentinel-1; Carbon dioxide; Aboveground Biomass; Multiple Satellite Data; Vegetation Index; Gradient Boosting; Carbon Emission Reduction; Enhanced Vegetation Index; Global Carbon Budget; Sentinel-2 Bands; Uydular; Ormanlar; Lazer radar; Tahmin; Bitki örtüsü haritalama; Sentinel-1; Karbondioksit; Yerüstü biyokütle; Çoklu uydu verileri; Bitki örtüsü endeksi; Eğim arttırma; Karbon emisyon azaltma; Küresel karbon bütçesi; Sentinel-2 bantları; Geliştirilmiş bitki örtüsü endeksi